Genome-wide analysis revealed the stepwise origin and functional diversification of HSDs from lower to higher plant species - Saleem, Noor; Aziz, Usman; Ali, Muhammad; Liu, Xiangling; Alwutayd, Khairiah Mubarak; Alshegaihi, Rana M.; Niedbała, Gniewko; Elkelish, Amr; Zhang, Meng (Frontiers in Plant Science, 2023)
Hydroxysteroid dehydrogenase (HSDs) is an oil-body sterol protein (steroleosin) with a NADP(H) binding domain that belongs to the short-chain dehydrogenase/reductase (SDR) superfamily. There are numerous studies on the characterization of HSDs in plants. However, thus far, the evolutionary differentiation and divergence analysis of these genes still remain to be explored. The current study used an integrated method to elucidate the sequential evolution of HSDs in 64 sequenced plant genomes. Analyses were conducted on their origins, distribution, duplication, evolutionary paths, domain functions, motifs composition, properties, and cis-elements. Results indicate that except for algae, HSD1 was widely distributed in plant species ranging from lower to higher plants, while HSD5 was restricted to terrestrial plants, and HSD2 was identified in fewer monocots and several dicot plants. Phylogenetic analysis of HSDs proteins revealed that monocotyledonous HSD1 in moss and ferns appeared closest to the outgroup, V. carteri HSD-like, M. musculus HSD1, and H. sapiens HSD1. This data supports the hypothesis that HSD1 originated in bryophytes and then in non-vascular and vascular plants, followed by HSD5 only in land plants. Gene structure analysis suggests that HSDs in plant species came up with a fixed number of six exons, and the intron phase was primarily, 0 1 0 0 and 0. Similarly, duplication analysis revealed that segmental duplications were the main reason for HSDs in plant species. Physicochemical properties suggest that dicotyledonous HSD1s and HSD5s were mainly acidic. The monocotyledonous HSD1s, HSD2s, dicotyledonous HSD2s, HSD3s, HSD4s, and HSD6s were mainly were basic, implying that HSDs in plants may have a variety of functions. Cis-regulatory elements and expression analysis revealed that HSDs in plants might have roles in several abiotic stresses. Due to the high expression of HSD1s and HSD5s in seeds, these HSDs in plants may have roles in fatty acid accumulation and degradation.